论中唐诗歌中的 “胡妆” = A study of “Hu makeup” in Middle Tang poetry - 赵思淇 Zhao, Siqi (Nanyang Technological University, 2020)
本文以中唐诗作为切入点，分析唐朝胡风盛行之时，“胡妆”在唐朝女性中的引领地 位，并对唐朝女性妆容的影响和改变。安史之乱后，“胡妆”逐渐消逝。通过诗人对 “胡妆”及胡文化(包括胡姬、胡乐和胡舞)在安史之乱前后的态度转变，发现唐人 不仅仅是对女性“胡妆”的排斥，而是对整个胡文化的重新审视，造成“胡妆”昙花 一现的文化现象。 This thesis focuses on how the “Hu makeup” was able to prevail in the midst of Hu cultural infiltration during the Tang dynasty from the perspective of Middle Tang poems. The An Lushan Rebellion was an important historical event which resulted in the rejection and thus disappearance of “Hu makeup” among the Tang females. In view of that, a comparison between “Hu makeup” and other cultural aspects of Hu including Hu dance, Hu dancers and Hu music was done. It was found that the dismissal attitude of Tang poets was not directed only at “Hu makeup”due to it belonging to a female realm but was addressed to the Hu and Hu-related things on the whole, thus resulting in the short-term flourish of “Hu makeup”.